Testbed Development of IoT-Based Volumetric 3D Air Monitoring for Indoor Artificial Photosynthesis Applications - NIK ZIN, NIK SYAZWA NAJIHAH; Saparudin, Faiz Asraf (Progress in Engineering Application and Technology, 2026)
The monitoring of indoor air quality (IAQ) is essential in the provision of healthy indoor environments, especially in the cases that need the careful regulation of the environment like in the artificial photosynthesis of indoors. Traditional single-point and two-dimensional (2D) methods used in monitoring are not adequate in describing both spatial and vertical differences in pollutants. This technological project introduces an Internet of Things (IoT)-based volumetric three-dimensional (3D) IAQ testbed with a series of M5Stack sensor nodes to detect TVOC, eCO2, hydrogen and ethanol concentrations, and real-time wireless data transmission to a cloud-based visualisation platform. As experimental analysis in the lecture hall proves, the 3D monitoring system suggested can effectively enhance the spatial resolution and allow the observation of localised areas of pollutant accumulation compared to 2D monitoring, which justifies its relevance as effective and applicable to the implementation of the 3D monitoring system in the practical and scalable performance of indoor air measurements and further smart environmental control in the future.